2019
DOI: 10.1007/s10964-019-01179-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the Peer Presence Effect on Heightened Adolescent Risky Decision-Making only Present in Males?

Abstract: Social neurodevelopmental imbalance models posit that peer presence causes heightened adolescent risk-taking particularly during early adolescence. Evolutionary theory suggests that these effects would be most pronounced in males. However, the small but growing number of experimental studies on peer presence effects in adolescent risky decision-making showed mixed findings, and the vast majority of such studies did not test for the above-described gender and adolescent phase moderation effects. Moreover, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…As this is not a direct replication study of a previously reported investigation, it may, however, also be dependent on precise methodological details and the specific demographics of our sample, e.g. on the fact that our sample did not include very young adolescents for whom strong susceptibility effects have been reported previously 4,5 (but also note 73 ). Our findings stress the importance of longitudinal designs for developmental psychology.…”
Section: Discussionmentioning
confidence: 95%
“…As this is not a direct replication study of a previously reported investigation, it may, however, also be dependent on precise methodological details and the specific demographics of our sample, e.g. on the fact that our sample did not include very young adolescents for whom strong susceptibility effects have been reported previously 4,5 (but also note 73 ). Our findings stress the importance of longitudinal designs for developmental psychology.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the findings, this study was seminal in demonstrating the feasibility of conducting an fMRI study that better approximated how adolescents make decisions "in real life"-in the presence of peers-than previous studies had done. This ecologically-informed approach has since been adopted in many other studies (e.g., Defoe, Dubas, Dalmaijer, & van Aken, 2020;van Hoorn, McCormick, Rogers, Ivory, & Telzer, 2018;Op de Macks et al, 2018) and forced the field to call into question whether the standard imaging approaches whereby participants are asked to complete cognitive tasks alone were actually capturing neural response to more ecologically-relevant behaviors such as risk-taking.…”
Section: Box 2 Ecological Validitymentioning
confidence: 99%
“…Our results are also in agreement with the finding in humans that social seeking is low in early adolescence ( Dubey et al, 2017 ) and additionally indicate that such a result may actually reflect that the surveyed group had met basic belongingness needs , making such findings applicable to a part rather than to all early-adolescents (which to some extent explains the discrepancy in the results of studies examining the developmental course of sociability). The results of the present study are also useful in the context of neurodevelopmental imbalance and evolutionary models of adolescent risky decision-making, with the former arguing that peer presence causes increased risk-taking, particularly during early adolescence ( Crone and Dahl, 2012 ), and the latter suggesting that effects would be the most pronounced in males for both early- and mid-adolescents ( Defoe et al, 2020 ). Motivational arousal due to peer presence could be expected in those who grow up in a social environment that does not support their social needs, particularly in early adolescence, so previous social experience in addition to age ( Crone and Dahl, 2012 ) and gender ( Defoe et al, 2020 ) should be taken into consideration when analyzing the influence of “the mere peer presence” in adolescence.…”
Section: Discussionmentioning
confidence: 78%
“…The results of the present study are also useful in the context of neurodevelopmental imbalance and evolutionary models of adolescent risky decision-making, with the former arguing that peer presence causes increased risk-taking, particularly during early adolescence ( Crone and Dahl, 2012 ), and the latter suggesting that effects would be the most pronounced in males for both early- and mid-adolescents ( Defoe et al, 2020 ). Motivational arousal due to peer presence could be expected in those who grow up in a social environment that does not support their social needs, particularly in early adolescence, so previous social experience in addition to age ( Crone and Dahl, 2012 ) and gender ( Defoe et al, 2020 ) should be taken into consideration when analyzing the influence of “the mere peer presence” in adolescence. This presumption is in agreement with the findings that the promotion of social wanting and the activation of the motivational/dopaminergic reward system in the midbrain happen in the presence of social cues in isolated both mice ( Matthews et al, 2016 ) and humans ( Tomova et al, 2020 ) and that a hyper-responsive motivational-reward system can undermine self-regulation in the presence of peers ( Albert et al, 2013 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation